Archaeology and the History of Early Islam: The First Seventy Years - Johns, Jeremy (Journal of the economic and social history of the Orient, 2003)
Abstract The rarity of material evidence for the religion of Islam during the first seventy years of the hijra (622-92 CE) has been used to attack the traditional positivist account of the rise of Islam. However, the earliest declarations of Islam are to be found on media produced by the early Islamic state. It is therefore mistake to read too much significance into the absence of such declarations prior to the formation of that state by Abd al-Malik (685-705 CE). There is little prospect that archaeology will uncover new evidence of Islam from the first seventy years. Le manque de données matérielles sur la religion de l'Islam pendant les sept premières décennies de l'hégire (622-92) a été utilisé pour réfuter la théorie positiviste traditionelle de l'essor de l'Islam. Cependant, les premières déclarations de l'Islam sont à trouver dans des oeuvres produites par l'Etat islamique à ses débuts. Il est donc erroné d'attribuer trop de sens à l'absence de telles déclarations avant la formation de cet Etat par Abd al-Malik (685-705). Il y a peu de perspectives de nouvelles découvertes archéologiques sur l'Islam des sept premières décennies.